Ten-Year Follow-Up of Collision Tumors Composed of Craniopharyngioma and Pituitary Adenoma: A Case Report and Literature Review - Takeshi Miyazaki; Kentaro Kowari; Hirotake Eda; Mizuki Kambara; Riruke Maruyama; Yasuhiko Akiyama (Case Reports in Medicine)
Although craniopharyngioma (CP) and pituitary adenoma (PA) are common tumors of the parasellar lesions, the coexistence of CP and PA is very rare. A 48-year-old male visited our hospital because of consciousness disturbance. The neuroimaging revealed a sellar tumor contact with a massive suprasellar cyst including calcification. Preoperative diagnosis was CP, and the patient underwent craniotomy to resolve the suprasellar mass effect. The histological examination disclosed adamantinomatous CP, and subsequently a transsphenoidal approach was chosen for the residual intrasellar tumor. Against expectations, the histological diagnosis was not CP but PA. The patient underwent gamma knife surgery for the residual tumor, and the postoperative course was good. After a 10-year follow-up, both lesions were still completely controlled. If we had suspected and diagnosed the tumor involved as not only CP but also PA at the first operation, the second operation could have been avoided because we would have chosen gamma knife surgery for the residual tumor. We should draw attention to this rare situation for differential diagnosis of parasellar tumor to avoid unnecessary surgery and to decide the best strategy for treatment. In addition, the biological behavior of collision tumors composed of CP and PA is probably the same as solitary CP or PA based on a long-term follow-up of our case.